An anilioid snake from the Upper Cretaceous of northern Patagonia - Gomez, Raul Orencio (2008)
We report the first record of anilioids from southern South America, a region where they do not live today. The fossils come from the Allen Formation (Late Campanian Early Maastrichtian) at Bajo Trapalcó and Bajo de Santa Rosa localities, Río Negro province, Argentina. The remains consist of several vertebrae, most of which belong to the mid posterior precloacal region of the column. Comparisons to other extant and extinct anilioid taxa indicate that these remains represent a new taxon, Australophis anilioides gen. et sp. nov. Australophis is morphologically closer to Palaeocene Hoffstetterella from Brazil and extant South American Anilius than to any other snake. These taxa might be closely related, in which case they would represent a lineage distinct from that including Cylindrophis and uropeltids. The two lineages must have diverged by the Late Cretaceous.